Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2008
DOI: 10.1007/s00436-008-0905-8
|View full text |Cite
|
Sign up to set email alerts
|

Insecticidal activity of major lichen compounds, (−)- and (+)-usnic acid, against the larvae of house mosquito, Culex pipiens L.

Abstract: In this research, (-)-usnic acid and (+)-usnic acid, commonly encountered lichen secondary metabolites, were evaluated for their insecticidal effects against the larvae of Culex pipiens L. (Diptera: Culicidae) under laboratory conditions. Both compounds showed strong larvicidal activity and caused 100% mortality on third-fourth larval stages of the species at 24 h at the doses of 5 and 10 ppm. Bioassays with (-)- and (+)-usnic acids against larvae of C. pipiens revealed that the LC50 values were 0.8 and 0.9 pp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(47 citation statements)
references
References 17 publications
0
43
1
Order By: Relevance
“…Both enantiomers of usnic acid, a widespread cortical dibenzofuran, exhibited strong larvicidal activity against the third and fourth instar larvae of the house mosquito (Culex pipiens), and larval mortality was dose-dependent (Cetin et al, 2008). Antifeedant activity and acute toxicity (injected into the larval haemolymph) of (-)-and (+)-usnic acids and vulpinic acid against the polyphagous larvae of the herbivorous insect Spodoptera littoralis have also been reported (Emmerich et al, 1993).…”
Section: Antiherbivore and Insecticidal Activitymentioning
confidence: 97%
“…Both enantiomers of usnic acid, a widespread cortical dibenzofuran, exhibited strong larvicidal activity against the third and fourth instar larvae of the house mosquito (Culex pipiens), and larval mortality was dose-dependent (Cetin et al, 2008). Antifeedant activity and acute toxicity (injected into the larval haemolymph) of (-)-and (+)-usnic acids and vulpinic acid against the polyphagous larvae of the herbivorous insect Spodoptera littoralis have also been reported (Emmerich et al, 1993).…”
Section: Antiherbivore and Insecticidal Activitymentioning
confidence: 97%
“…The insecticidal activity of the AU has also been the subject of scientific studies. Cetin et al (2008) investigated the insecticides effects of AU against Culex pipiens mosquito larvae and determined the insecticidal activity by bioassays. In this study a homology model was built and evaluated for the A. aegypti glutathione Stransferase 2 (AaGSTE2).…”
Section: Introductionmentioning
confidence: 99%
“…Usnic acid also serves as a strong toxicant toward certain insects such as mosquitoes. It has been reported that usnic acid (5 and 10 ppm) killed all the larvae of certain species of mosquitoes on their 3rd-4th stages, suggesting that it might be developed as a novel natural insecticide (54). In addition to the toxicity toward animals, usnic acid displays phytotoxicity as well.…”
Section: In Vivo Toxicity Datamentioning
confidence: 99%